Transcriptional regulation of the dlt operon in Enterococcus faecalis and further characterization of a dlta mutant - Allen, Darin (Kansas State University, 2008)
Enterococcus faecalis, a gram-positive member of the mammalian gastrointestinal flora, emerged as an important contributor to nosocomial infections and antibiotic resistance gene transfer. Lipoteichoic acid (LTA), a vital component of gram-positive cell walls, has been reported to function in numerous cellular processes, ranging from maintenance of cation homeostasis and virulence to modulating function and presentation of wall proteins such as adhesins and autolysins. Interestingly, LTA can be covalently modified by the addition of D-alanyl ester residues, which appear to help regulate its function by altering surface charge. In E. faecalis the process of esterification is catalyzed by four proteins encoded by the dlt operon. Mutants lacking a functional dlt operon display the inability to incorporate D-alanyl residues on LTA and are thus deficient in their ability to regulate the anionic charge of the outer envelope in response to extracellular cues. Recent evidence suggests that two-component systems are responsible for sensing environmental conditions and regulating dlt operon expression. Utilizing a reporter construct with the upstream promoter region of dlt fused to lacZ, we were able to determine how extracellular stimuli affect transcription of this operon by measuring [Beta]-galactosidase activity. Furthermore, we were able to identify specific response regulators important for bile salt, magnesium and polymyxin B signaling.
Keywords: Enterococcus; Faecalis; Transcription; Regulation; Biology, Microbiology (0410)